Answer:
[tex]\frac{2(x-1)(2x+9)}{(x-3)(x-2)}[/tex]
Step-by-step explanation:
[tex]\frac{4x}{(x-3)}+\frac{6}{(x+2)}[/tex]
= [tex]\frac{4x(x+2)}{(x-3)(x+2)}+\frac{6(x-3)}{(x+2)(x-3)}[/tex]
Now we have done the denominators of each term of the expression equal.
Further we add the terms,
[tex]\frac{4x(x+2)}{(x-3)(x+2)}+\frac{6(x-3)}{(x+2)(x-3)}[/tex]
= [tex]\frac{4x(x+2)+6(x-3)}{(x-3)(x+2)}[/tex]
= [tex]\frac{4x^{2}+8x+6x-18}{(x-3)(x+2)}[/tex]
= [tex]\frac{4x^{2}+14x-18}{(x-3)(x-2)}[/tex]
Now factorize the numerator of the fraction.
4x² + 14x - 18 = 2(2x² + 7x - 9)
= 2(2x² + 9x - 2x - 9)
= 2[x(2x + 9) - 1(2x + 9)]
= 2(x - 1)(2x + 9)
Therefore, [tex]\frac{2(x-1)(2x+9)}{(x-3)(x-2)}[/tex] will be the answer.